Radicalizing CO by mononuclear palladium(I) - Bruckhoff, Tim; Ballmann, Joachim; Gade, Lutz H. (Angewandte Chemie. International edition, 2024)
A mononuclear, T-shaped palladium(I) d9 metalloradical (3), stabilized by a bulky carbazole-based PNP-ligand, was obtained by reduction of palladium chloride or thermal Pd−C bond homolysis of the corresponding neopentyl complex. Pressurizing with CO gave the Pd(I) carbonyl complex, which was structurally characterized by X-ray diffraction. Delocalization of the unpaired electron to the carbonyl carbon was detected by EPR spectroscopy and theoretically modeled by DFT and ab initio methods. The partially reduced and radicalized CO slowly reacts with di(tert-butyl) disulfide under homolytic S−S cleavage and C−S bond formation to give the corresponding metallathioester.
Online verfügbar: 18. März 2024, Version des Artikels online: 4. April 2024
Gesehen am 26.07.2024